Assessing thermal comfort in urban squares in humid subtropical climate: A structural equation modelling approach. (1st February 2023) - Manavvi, S.; Rajasekar, E.
Abstract: This study examines the factors influencing thermal comfort in urban squares of India. Four designed squares dominated by recreational cum commercial activities were studied during summer. The study establishes that comfort is a finely graded perceptual construct determined by a multitude of factors. Relative weightages of varied factors influencing thermal comfort are determined using structural equation modelling (SEM). In addition to the perceived micrometeorological conditions, socio-demographic factors, prior thermal history as well as perception pertaining to varied open space attributes (e.g. environmental features, spatial, aesthetics aspects) were examined. 409 valid responses were collated from the chosen squares and used for formulating the path model. The perception of open space attributes (e.g. environmental features; spatial and aesthetic aspects) had a comparatively higher effect on subjective thermal comfort assessment. Among the open space attributes, perception of environmental features was the most decisive factor. The findings of the study provide valuable insight for improving the thermal environment of urban squares. Highlights: Path model formulated to present factors influencing outdoor thermal comfort. Relative weightages of factors influencing outdoor thermal comfort determined. Perception of site attributes decisively influences thermal comfort outdoors. Environmental features have a stronger influence on thermal comfort than other factors.